Highly Diastereo- and Enantioselective Synthesis of Isoxazolone-Spirooxindoles via Squaramide-Catalyzed Cascade Michael/Michael Addition Reactions - Wang, Yu; Du, Da-Ming (Journal of organic chemistry, 2020)
A highly enantioselective [3+2] annulation of 3-((2-oxoindolin-3-yl)oxy)acrylates with isoxazol-5(4H)-ones has been accomplished by squaramide-catalyzed cascade Michael/Michael addition reactions under mild conditions. The corresponding isoxazolone-spirooxindoles with four continuous stereocenters were obtained in moderate to high yields with excellent stereoselectivities (up to >20:1 dr, 97% ee). The synthetic practicality of this methodology was illustrated by performing the reaction on a gram scale with the same efficiency and stereoselectivity. Meanwhile, the isoxazol-5(4H)-one ring could be opened by the reaction with iron powder and ammonium chloride, and the corresponding acyl derivative can be obtained with a maintained yield and stereoselectivity.